Pengaruh El Niño Southern Oscillation (ENSO) dan Indian Ocean Dipole (IOD) Terhadap Curah Hujan dan Korelasinya dengan Consecutive Dry Days (CDD) Provinsi Sumatera Selatan dari Tahun 1981-2020 - Melly Ariska; Hamdi Akhsan; Muhammad Muslim; Sudirman Sudirman; Kistiono Kistiono (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2022)
El Niño Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD)` are events where the phenomenon of rising and falling sea surface temperatures becomes unnatural. Stronger events where the sea surface temperature anomaly becomes large, then this disrupts local fish and bird populations. The ENSO and IOD phenomena also affect rainfall in several parts of Indonesia. This study analyzed the effect of ENSO and IOD phenomena on rainfall in South Sumatra Province from 1981 to 2020 and the correlation between Consecutive Dry Days (CDD) and Rainfall in South Sumatra Province for the last 40 years. ENSO data and IOD data were analyzed against rainfall data analyzed using a simple linear regression method and associated with CDD in South Sumatra Province with the correlation method. In addition, a correlation analysis was also carried out between the Niño 3.4 index and the Dipole Mode Index (DMI) with rainfall at two stations, namely the Palembang Climatology Station and the Sultan Mahmud Badaruddin II Meteorological Station to determine how much influence the ENSO and IOD phenomena had on rainfall in the Sumatra Province. South. The results of the analysis show that the effect of ENSO and IOD on rainfall at each station is generally not significant. The state of rainfall in the Province of South Sumatra for the last 40 years is almost not influenced by El Nio and La Nia. This is presumably due to the location of the South Sumatra Region which is in the Munsonal area. Monsoon areas are characterized by a unimodial type of rainfall (one peak of the rainy season) where in June, July and August the dry season occurs, while December, January and February are the wet months. The remaining six months is a transitional or transitional period (three months of transition from dry season to rainy season and three months of transition from rainy season to dry season).